Geoindicators For Monitoring Canada's National Parks System - Welch, David (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2003)
Summary Parks Canada reports on the state of national parks using a framework based on indicators of ecosystem structure, functions and stresses. Parks Canada can add geoindicators to this framework by drawing from those endorsed by the International Union of Geological Sciences and the suite adopted by Canada's Ecological Monitoring and Assessment Network - 28 indicators in all. I considered five other potential geoindicators of rapid environmental change, namely the built environment, extreme events, marine nearshore environments, snow avalanches and tufa accumulation. From the combined total of 33 geoindicators I chose a short list of ten based on relevance to ecosystem understanding, linkage to other measures, and practicality for long-term adoption. To represent structure Ipropose dunes, glaciers, lakes, shorelines and wetlands. For processes I propose frozen ground activity, groundwater level, mass movements, stream flow and soil water quality. For stresses I propose the built environment.